A Petrographic Atlas of Ophiolite An example from the eastern India-Asia collision zone - Ghose, Naresh Chandra; Chatterjee, Nilanjan; Fareeduddin (Springer India : Imprint: Springer, 2014)
The book is a thoughtful discussion with scientists studying convergent plate boundaries such as the well-known, active India-Eurasia collision zone. It provides a comprehensive collection of petrographic images of ophiolitic rocks exhumed from oceanic lithosphere and mantle at the India-Asia plate boundary. Ophiolite is exposed in the northwestern Himalayas, eastern Indian plate margin and Andaman-Nicobar Islands. At the eastern margin, it occurs in a narrow strip comprising mantle peridotite tectonite, cummulate peridotite-gabbro-plagiogranite-anorthosite, mafic dyke, volcanics and oceanic sediments. Low temperature/high pressure rocks including blueschists and eclogites were extensively studied recently. Ophiolite derived sediments and podiform chromites will also be discussed to provide complete details. Supplemental maps, geological sections, field sketches and photographs will explain the structure, stratigraphy, ore mineralization, and metamorphic history.